Pengaruh Variety Seeking dan Minat Beli Terhadap Keputusan Pembelian - Baihaqi, Ahmad Imam; Sartika, Fani; Supiati; Elizabeth; Nurlina (Jurnal EMT KITA, 2025)
The purpose of this research is to analyze and test the influence of Variety Seeking and purchase interest on the decision to purchase Zalora products. This research uses a quantitative method with regression analysis. The sampling technique uses purposive sampling and the number of samples as many as 71 respondents was obtained by distributing questionnaires to consumers who have shopped at Zalora. The data was analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results of this research show that purchase interest has a significant effect on the decision to purchase Zalora products, while variety seeking does not have a significant effect on the decision to purchase Zalora products. The results of this research can be used as evaluation material for the management of companies that trade fashion products to pay more attention to purchase interest so that the decision to purchase Zalora products can be improved.